Wither the Roses of Yesteryears: An Exploratory Look into the Lives of Moro Women During the Colonial Period - Abubakar, Carmen A. (Review of Women's Studies; Vol 8 No 2 (1998): Review of Women's Studies Volume VIII, Number 2 (July-December 1998))
---